Raising Awareness for Gender Equality in Hindu Marriage - Kaydani, Maryam (European Journal of Multidisciplinary Studies, 2016)
The Hindu marriage has been one of the controversial issues among activities. Marriage in Hindu community is considered as holy and very significant social institution. In real, it is a commercial exchange and at large a marketplace populated by high demanding groom family. The paper aims to give a comprehensive account of problems that Hindu girls encounter during their marriage and within their marriage life. Apparently, Hindu marriage is between two families rather two people. More or less girls have no right to object. As a result girls mostly get married at earliest opportunity and they are forced into relationship as such most of marriage is based on parent’s decision rather than mutuality of sentiment or emotional attachment. Therefore, prepubescent girls are often oppressed by bridegroom and his family members. In this sort of relationship, girls are financially dependent which develop their suppression. Data for this paper has drawn from in-depth interviews conducted with 120 married women of aged 12-20 years living in two Indian states who got married since 2005. Participants were randomly selected for interview if the woman was married before the ages of 15 years. Findings underscore the need to raise awareness of the negative outcomes of child marriage and to build support among girls and their families for delaying marriage, to enforce existing laws on the minimum age at marriage and to encourage other authorities to support young women in negotiating with their parents to delay marriage and eliminate child marriage.